TRANSFORMASIONAL LEADERSHIP UNTUK PENINGKATAN MUTU PENDIDIKAN ANAK USIA DINI - Nofi Puspita Sari; Ahmad Ridani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Early Childhood Education (ECE) plays a crucial role in supporting children's character development, intelligence, and overall growth during the golden age period. The quality of ECE services is strongly influenced by the leadership of school principals or institution leaders in managing educational resources. Transformational leadership is considered an effective approach to improving educational quality, as it emphasizes the ability of leaders to inspire, motivate, empower, and develop the potential of all organizational members. This article examines the concept of transformational leadership and its contribution to improving the quality of early childhood education. The findings indicate that transformational leadership enhances teacher competence, promotes a positive work culture, encourages learning innovation, strengthens parental involvement, and supports the creation of a high-quality educational environment. Therefore, transformational leadership is an important strategy for achieving sustainable quality improvement in early childhood education.